Re-evaluation of the impact of wall retention on Tritium-self-sufficiency in fusion reactors - K. Schmid (Nuclear Fusion)
In recent years several publications have claimed that the retention of tritium (T) in the first wall armor material poses a limitation on when a fusion reactor becomes T-self-sufficient. While the prediction on wall retention therein are correct, the model applied to assess the T-self-sufficiency is based on wrong assumptions and thus, the importance of T-retention in the first wall is greatly overestimated. In this publication the predictions on T-retention in the first wall armor components are included in state of the art residence time models of the entire T-cycle. These calculations show that T-wall-retention only affects T-self-sufficiency when the T-breeding ratio (TBR) is so low that the power plant is only marginally T-self-sufficient. For TBR values that allow for a finite T-doubling time and maintain a T-reserve inventory, the T-production must be so high, that the T-wall-retention is insignificant. The paper will explain the error in the previous T-self-sufficiency estimates, how to correct them and what this means for the conclusions drawn by previous publications. Then an augmented residence time model will be presented, that can include diffusion/trapping model based, time dependent wall loss data. This augmented model results in orders of magnitude higher T-retention in the first wall compared to current assumptions in residence time models. Still, it is negligible compared to the T-content in the entire T-cycle. Thus it can be concluded that based on current material data T-retention in the first wall armor will not affect T-self-sufficiency.